Physical modeling of HZO-based ferroelectric field-effect transistors with a WOx channel - Wen, Xin; Halter, Mattia; Bégon-Lours, Laura; Luisier, Mathieu (Frontiers in Nanotechnology, 2022)
The quasistatic and transient transfer characteristics of Hf0.57Zr0.43O2 (HZO)-based ferroelectric field-effect transistors (FeFETs) with a WOx channel are investigated using a 2-D time-dependent Ginzburg-Landau model as implemented in a state-of-the-art technology computer aided design tool. Starting from an existing FeFET configuration, the influence of different design parameters and geometries is analyzed before providing guidelines for next-generation devices with an increased “high (RH) to low (RL)” resistance ratio, i.e., RH/RL. The suitability of FeFETs as solid-state synapses in memristive crossbar arrays depends on this parameter. Simulations predict that a 13 times larger RH/RL ratio can be achieved in a double-gate FeFET, as compared to a back-gated one with the same channel geometry and ferroelectric layer. The observed improvement can be attributed to the enhanced electrostatic control over the semiconducting channel thanks to the addition of a second gate. A similar effect is obtained by thinning either the HZO dielectric or the WOx channel. These findings could pave the way for FeFETs with enhanced synaptic-like properties that play a key role in future neuromorphic computing applications.